The impact of insider trading on forecasting in a bookmakers' horse betting market - Adi Schnytzer; Martien Lamers; Vasiliki Makropoulou (Bar-Ilan University, Department of Economics, 2009)
This paper uses a new variable based on estimates of insider trading to forecast the outcome of horse races. We base our analysis on Schnytzer, Lamers and Makropoulou (2008) who showed that inside trading in the 1997-1998 Australian racetrack betting market represents somewhere between 20 and 30 percent of all trading in this market. They show that the presence of insiders leads opening prices to deviate from true winning probabilities. Under these circumstances, forecasting of race outcomes should take into account an estimate of the extent of insider trading per horse. We show that the added value of this new variable for profitable betting is sufficient to reduce the losses when only prices are taken into account. Since the only variables taken into account in either Schnytzer, Lamers and Makropoulou (2008) or this paper are price data, this is tantamount to a demonstration that the market is, in practice, weak-form efficient.
Keywords: 330; Insiderhandel; Glücksspiel; Pferdesport; Prognoseverfahren; Australien